Effect of Styrene Butadiene Styrene on Properties of Open-Graded Asphalt Concrete Mixtures - Namaa, Mohammed Muslim; Qasim, Zaynab I.; AlHelo, Karim H. Ibrahim (Al-Nahrain Journal for Engineering Sciences, 2022)
Open graded asphalt mixture is becoming more widespread where it is applied for various purposes, e.g. drainage of rainwater effectivity, traffic safety (high skid resistance), and controlling pollution noise. However, it has many other disadvantages, of which low stability, high stripping, and moisture sensitivity. The research aims to study the effect of styrene butadiene styrene SBS addition on the volumetric and mechanical properties of open graded mixture. In this research one type of aggregate with gradation (12.5 mm NMAS), asphalt of penetration grade (40/50), and cement as filler were used. Optimum asphalt content was selected based on the criteria of air voids content, asphalt drain down, permeability, and abrasion resistance (for aged and un-aged) samples. Other properties of open-graded mixtures, such as indirect tensile strength (ITS), moisture susceptibility, Marshall stability and flow were evaluated. The results show that addition of polymer (SBS) leads to an enhancement in the properties of the modified mixtures. There is an improvement in Marshall parameters. Also, a slight decreasing is noticed for permeability and air voids. For Cantabro abrasion loss (aging and un-aging condition), the abrasion resistance is increased, the drain down of asphalt is decreased from original mixture by addition of SBS. Finally, the moisture sensitivity is improved indicating that modified mixes becomes more resistant to water damage.